Semi-automated data provenance tracking for transparent data production and linkage to enhance auditing and quality assurance in Trusted Research Environments - Katherine O'Sullivan; Milan Markovic; Jaroslaw Dymiter; Bernhard Scheliga; Chinasa Odo; Katie Wilde (International Journal of Population Data Science)
Introduction We present a prototype solution for improving transparency and quality assurance of the data linkage process through data provenance tracking designed to assist Data Analysts, researchers and information governance teams in authenticating and auditing data workflows within a Trusted Research Environment (TRE).